Government Responses to Fiscal Austerity: The Effect of Institutional Fragmentation and Partisanship. (February 2014) - Jensen, Carsten; Mortensen, Peter B.
How does the institutional context affect government responses to fiscal austerity? Despite the "institutional turn" in political science, we still possess an incomplete understanding of the relationship between a core aspect of the institutional setting of countries—namely institutional fragmentation—and the policy consequences of fiscal pressure. The article advances research on this question by integrating theories on the blame-avoidance effect of institutional fragmentation with theories on the effect of party constituencies on social policies. The result is a set of novel hypotheses about the conditional effects of institutional fragmentation that are tested empirically on quantitative time series data on unemployment protection from 17 advanced democracies. The analyses show that institutional fragmentation is an important determinant of government responses to fiscal austerity, but the effect depends on the partisan composition of the government.